Red as blood, white as snow, black as crow: chromatic symbolism of womanhood in fairy tales - Vaz da Silva, F. (2019)
Since Brent Berlin and Paul Kay's classic study on Basic Color Terms, the universal chromatic trio of white, red, and black became a matter of scholarly interest. This article examines uses of this chromatic trio to depict ideal womanhood in European fairy tales. Chrétien de Troyes wrote that the sight of three drops of blood on snow reminds Perceval of his sweetheart; seven centuries later, the Grimms presented a queen wishing for a tricolor daughter after looking at three drops of blood on the snow. This image is tenacious in the fairy-tale realm, and the time seems ripe for addressing it.